Asymptotic Representations for Some Classes of Solutions of Ordinary Differential Equations of Order $n$ with Regularly Varying Nonlinearities - Evtukhov, V. M.; Klopot, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Existence conditions and asymptotic (as $t \uparrow ω (ω ≤ +∞)$) representations are obtained for one class of monotone solutionsof an $n$th-order differential equation whose right-hand side contains a sum of terms with regularly varying nonlinearities.